Creating authentic video scenarios for use in prehospital research. (May 2017) - Preston, Christopher; Carter, Bernie; Jack, Barbara; Bray, Lucy
Highlights: Nominal group technique used with expert panels can create authentic video scenarios. Authenticity of contextual cues in video scenarios can be achieved using subtext. Authenticity in video scenarios facilitates connectivity and participant buy-in. Authentic video scenarios may offer an alternative data collection tool to simulation. Abstract: Video scenarios have been used to explore clinical reasoning during interviews in Think Aloud studies. This study used nominal group technique with experts to create video scenarios to explore the ways paramedics think and reason when caring for children who are sick or injured. At present there is little research regarding paramedics' clinical reasoning with respect to performing non-urgent procedures on children. A core expert panel identified the central structure of a prehospital clinical interaction and the range of contextual factors that may influence a paramedic's clinical reasoning [the way in which information is gathered, interpreted and analysed by clinicians]. The structure and contextual factors were then incorporated into two filmed scenarios. A second panel of clinical practice experts, then critiqued the body language, spoken word and age appropriate behaviours of those acting in the video scenarios and compared them against their own experience of clinical practice to confirm authenticity. This paper reports and reflects on the use of nominal group technique to create authentic video scenarios for use in prehospital research.